Notice: PSPB Articles by Authors With Retracted Articles at PSPB or Other Journals: Stapel, Smeesters, and Sanna. (January 2014) - Funder, David; ,
Numerous articles by the social psychologists Diederick Stapel, Dirk Smeesters, and Lawrence Sanna have been retracted in several different journals. The present notice reports the results of an investigation into papers authored or coauthored by these individuals, and published in Personality and Social Psychology Bulletin, that have not been retracted. The status of these papers range from data confirmed as legitimate by coauthors to, in many cases, being unknown as to their legitimacy. Given the lack of information in the latter cases, there is insufficient basis to recommend retraction at this time. Researchers using the results of these papers in their own work are advised to take the information reported in this notice into account.